Late medieval Vlachs in the western Balkans: orality, society and the limits of collective identities - Pijović, Marko (Balcanica Posnaniensia. Acta et studia, 2021)
This paper explores the social structures of late medieval Vlachs – particularly the ones inhabiting the Western Balkans (the Dinaric Alps) – in order to determine how collective identities were shaped and reproduced in medieval oral cultures. Southeast European historiographies have often portrayed the Balkan Vlachs as a unitary group and the label „Vlach” as representing a single, homogenous social entity during most of the Middle Ages. Still, social groups cannot exist and function without regular communication – oral or written – between their members. Oral cultures are based on verbal communication and are therefore bound by its specific nature, given that it requires continuous personal contact and oral transfer of information for communication and society to function properly. Literate cultures on the other hand tend to rely on written communication to a considerable extent and given that it allows for information to be conveyed impersonally (by text) its range is (at least in theory) almost limitless – as it is the level of (il)literacy that represents the main communicative and social limit in literate societies. Having in mind the abovementioned communicative and social limits of orality and the fact that it was the predominant if not exclusive form of communication among transhumant pastoralists such as the medieval Balkan Vlachs this paper argues that the range/scope of their group identities and collective identifications was rather limited. Furthermore, this paper discusses the types of collective identities utilized by Vlachs, questioning whether they ever shared a common „Vlach identity” given the fact that the social identity of the medieval people known as „the Vlachs” was primarily shaped and defined from the „outside” and „above” – by state intervention and a legal frame that was forced upon them. The Vlachs in the Medieval Balkans, and particularly in its western part, generally did not possess political authority and power, nor did they have the material resources and literary traditions allowing them to form more complex and enduring communication networks that would in turn have resulted in group identity formation on a larger scale. During the Early Middle Ages the Vlachs were „Vlachs” primarily because they were labelled as such and considered to be a distinct category of population by their Slavic (and later Byzantine) neighbours and overlords, and not necessarily because they originally defined themselves as such. This is not to say that gradually, during the course of the Middle Ages, the bearers of the „Vlach” name could not have started to identify themselves as „Vlachs” by accepting this foreign name (xenonym) as their preferred group name (autonym). Still, when this finally did happen it did not imply a „universal” Vlach identity in the medieval Balkans. Given the communicative limits of oral cultures as well as the Vlachs’ position as legal and political „objects” rather than „subjects” it seems most likely that the medieval Balkans witnessed a simultaneous existence of a multitude of „Vlachnesses” which were usually unrelated and unaware of each other.